1981
DOI: 10.1088/0031-9155/26/2/006
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetry with a diamond operating as a resistor

Abstract: A very pure diamond with contacts of graphite has a linear current-voltage characteristic when subjected to irradiation. The resistivity is inversely proportional to the dose rate and the sensitivity is extremely high for gamma- and X-rays and electron beams. It is concluded that diamond resistors are suitable for clinical radiation dosimetry. This conclusion is also based on earlier work in which diamonds were used as pinpoint counters.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

1988
1988
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(30 citation statements)
references
References 14 publications
0
30
0
Order By: Relevance
“…Thus diamond crystals suitable for radiation dosimetry need a certain concentration of impurities, but too much will cause the diamond to be insensitive and to suffer from polarization effects. Suitable diamond crystals for dosimetry are of the colorless type IIa 11 , 12 with a low nitrogen concentration of less than 1019.15emcm3.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus diamond crystals suitable for radiation dosimetry need a certain concentration of impurities, but too much will cause the diamond to be insensitive and to suffer from polarization effects. Suitable diamond crystals for dosimetry are of the colorless type IIa 11 , 12 with a low nitrogen concentration of less than 1019.15emcm3.…”
Section: Introductionmentioning
confidence: 99%
“…Studies in contact technology have been reported by several authors 5 , 6 , 10 , 11 . It is necessary to find contact materials which do not lead to an energy dependence of the diamond detector in high‐energy dosimetry.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, its large bandgap (5.5 eV), radiation hardness, optical transparency, large saturated carrier velocities, and low atomic number, make diamond a very attractive candidate for the detection of ionizing radiation in applications as dosimeter as well as in high energy experiments. Diamond as ionization detector was proposed by Hofstadter in the 1940s [62], and several studies were performed for the characterization of the material and for applications in nuclear physics and dosimetry [63,64]. However, these detectors found restricted usage due to limitations of natural diamonds, mainly the small size and the uncontrolled material characteristics [65].…”
Section: Diamondmentioning
confidence: 99%
“…The potential use of such material for ionizing radiation dosimetry by thermoluminescence have been investigated since 1980. Natural diamond has been examined but thermoluminescence (TL) signal was very weak and not reproducible [3,4]. Diamond (Z = 6) with its atomic number being close to the effective atomic number of biological tissue (Z = 7.42) can be considered as a tissue-equivalent material.…”
Section: Introductionmentioning
confidence: 99%